A Case Study on Mobile-Blended Collaborative Learning in an English as a Foreign Language (EFL) Context - Avci, Hulya; Adiguzel, Tufan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
As learning a foreign language poses a number of challenges for the students, it has become indispensable to search for “optimal” conditions to enhance opportunities of engaging in the target language. Within this context, the Mobile-Blended Collaborative Learning model has been integrated in and out of the classroom learning in order to enable language learners to practice English by means of collaborative, authentic language activities based on project-based learning approach. The purpose of this study was to explore the effects of using mobile instant messaging application, WhatsApp on the language proficiency of EFL students.  Participants (N = 85) were enrolled in five upper-intermediate prep classes at a foundation university in Istanbul and took part in a seven-week Project Work. Data were collected through semi-structured interviews and focus group discussions, self- and peer evaluations of group work, a rubric for assessing project work, and log files of WhatsApp conversations. Results revealed practicing English in an authentic setting where the students used the target language for a real purpose facilitated their language learning, improved their communication skills and vocabulary knowledge, and made them recognize colloquial English. Additionally, instant messaging in an informal platform for educational purposes had positive effects on their performance and the quality of their work.